Current Account Dynamics and the Terms of Trade: Harberger-Laursen-Metzler Two Generations Later - Persson, Torsten (Journal of Political Economy, 1985)
This is a study of the current account dynamics resulting from the savings and investment dynamics in a small open economy which is subject to exogenous changes in its terms of trade and in world interest rates. Anticipated and unanticipated, as well as temporary and permanent, terms of trade changes have very different effects. There is, however, a general tendency towards cycles in both savings and investment, which gives rise to cycles in the current account. It is shown that the classic Harberger-Laursen-Metzler effect on saving of a terms of trade deterioration can have any sign for plausible parameter values, both for temporary and permanent disturbances.